The Banality of Ghosts. Searching for Humanness with Joshua Oppenheimer in THE ACT OF KILLING The Banality of Ghosts - Lucien van Liere (Journal for Religion, Film and Media, 2018)
In The Act of Killing, (Joshua Oppenheimer, ID, DK 2012), Joshua Oppenheimer searches for humanness by assessing the rituals, routines and grammar of former perpetrators who played a role during the 1965/6 genocide in Medan, Indonesia. This article puts The Act of Killing in the context of Oppenheimer's writings on film and violence and explores how this film negotiates humanness by working with a missionary paradigm of expressive guilt that not only serves the director, but also a critical audience with a happy ending.